Uji In-Vitro Hidroksiapatit Berpori Menggunakan Larutan Simulated Body Fluid (SBF) Dengan Variasi Penambahan Pati Kentang - Deska Deska; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One method of biological hydroxyapatite testing is in vitro, which is testing material outside the system or not directly on living things. Some ways include using cell culture media, test tubes or Simulated Body Fluid (SBF) solutions. The purpose of this study was to test in-vitro porous hydroxyapatite with variations in potato starch using a Simulated Body Fluid (SBF) solution. This research was conducted by mixing 4 and 6 grams of potato starch with 12 grams of HA, 35 mL aquadest. The slurry is stirred at 150 rpm for 3 hours. Then the slurry is put into a mold and dried in an oven at 80˚C for 24 hours and 120˚C for 8 hours. The dried green bodies are burned at 600°C and the sintering process at 1250°C. Furthermore porous hydroxyapatite was soaked using the SBF solution for 28 days. Samples were analyzed using XRD analysis and SEM analysis. Based on SEM analysis apatite layers were formed in all samples. Samples had an average pore diameter of 96.66 μm and 105.8 μm. Where the crystallinity value of the samples obtained by 73.75% and 77.19%. The addition of potato starch to the sample can enlarge pore diameter, facilitate ion exchange and increase sample resistance during the immersion process using SBF solution.Keywords: potato starch, hydroxyapatite, Simulated Body Fluid, in-vitro test